answersLogoWhite

0


Best Answer

The reciprocal of a + bi is a - bi:

1/(a + bi) since the conjugate is a - bi:

= 1(a - bi)/[(a + bi)(a - bi)]

= (a - bi)/[a2 - (b2)(i2)] since i2 equals to -1:

= (a - bi)/(a2 + b2) since a2 + b2 = 1:

= a - bi/1

= a - bi

User Avatar

Wiki User

โˆ™ 2009-08-04 20:35:59
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the reciprocal of a plus bi if a2 plus b2 equals 1?
Write your answer...
Submit
Related questions

If a2 plus b2 equals c2 then c2 equals b2 equals?

a2


Why is the Pythagorean therm a2 plus b2 equals c2 not a plus b equals c?

l a2 b2 is c2!!Its completely norma


A2 plus b2 equals c2 is an example of?

Pythagorean Theorem


If a2 plus b2 equals c2 then the triangle is?

a right triangle


What are the lengths of and A plus B in a right triangle if C equals 8?

A2 + B2 = C2 If C=8, then A2 + B2 = 64


How do you calucate a2 plus b2?

a2+2a2b+2ab2+b2


What is the algebraic formula for a2 plus b2 equals c2?

You just typed it.


If a plus b plus c equals x plus y plus z then prove a2 plus b2 plus c2 equals x2 plus y2 plus z2?

a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z


Who introduced a2 plus b2 equals c2?

Pythagoras' theorem for a right angle triangle.


How do you solve a2 plus c2 equals b2 and a equals 10 and your c is 30?

All you need to do is substitute the given values of a and c into the equation, then solve for c: a2 + c2 = b2 102 + 302 = b2 100 + 900 = b2 b2 = 1000 b = √1000 b = 10√10


CosA equals a2 plus c2 minus b2 by 2ac what is this formula?

This is known as the Cosine Rule.


If a2 plus b2 plus c2 - ab - bc - ca equals 0 then prove a equals b equals c?

a2 + b2 + c2 - ab - bc - ca = 0 => 2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca = 0 Rearranging, a2 - 2ab + b2 + b2 - 2bc + c2 + c2 - 2ca + a2 = 0 => (a2 - 2ab + b2) + (b2 - 2bc + c2) + (c2 - 2ca + a2) = 0 or (a - b)2 + (b - c)2 + (c - a)2 = 0 so a - b = 0, b - c = 0 and c - a = 0 (since each square is >=0) that is, a = b = c


Factor A2 plus 4a plus 4 - b2?

a2 - 4a + 4


Is a squared plus b squared the same as a plus b squared?

No. If you expand (a + b)2 you get a2 + 2ab + b2. This is not equal to a2 + b2


Math inventor of a2 plus b2 equals c2?

Pythagoras. That's why it's called the Pythagorean Theorem.


What is Pythagoras famous quotes?

a2+b2=c2 a squared plus b squared equals c squared


Who first proposed the therom a2 plus b2 equals c2?

Pythagoras, the Greek Mathematician. The Pythagorean theorem (P Theorem) ~ a2 + b2 = c2 Also used to find the hypotenuse of certain triangles.


What theoremcontains the formula c2 equals a2 plus b2?

Pythagoras' theorem. This is telling us that, for a right angled triangle, the square of the hypotenuse (c2) is equal to the sum of the square of the other two sides (a2 + b2).


How do you simplify the square root of a squared plus b squared?

sqrt(a2 + b2) can't be simplified. Neither can (a2 + b2) .


Chords lyre of lupang hinirang with lyrics?

Lupang hinirang intro:g f# a2 g d/a2 b2 c2 b2 a2 b2 g/g f# a2 g d/ a2 b2 c2 b2 a2 g/g f# a2 g d/a2 b2 c2 b2 a2 b2 g/ g f# a2 g d/a2 b2 c2 b2 a2 g/ refrain:g f# g a2 a2 d d a2 a2 d d/b2 c2 b2 e2 d2/ g f# g a2 a2 d d a2 a2 d d/b2 c2 b2 a2 b2 a2 g/(2x) g f# g c2 c2 d2 d2 e2 d2 c2 d2 e2/f2 e2 d2 e2 c2 d2 b2 b2 c2r/(2x)


How do you solve x squared plus 9 equals to zero?

The answer is x = 3i and x = -3i. {Where i= √(-1)}An expression in the form a2 - b2 can be factored into (a - b)(a + b), but you have a2 + b2 so this factors into (a - bi)(a + bi). Check by multiplying the binomials: a2 + abi - abi - (bi)2 the [abi]'s cancel, and i2 = -1, so you have a2 + abi - abi - -b2 which is a2 + b2, so it checks out. In this case, a is x and b is 3.


How do you calculate in Excel commission of 7 percent on all sales that are at least 25 percent above cost?

Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )Assuming the sale is in B2 and the cost in A2, you could use the following formula to do it:=IF( B2>=A2*1.25, B2*7%, 0 )


How do you solve a to the 3rd power plus b to the 3rd power divided by a plus b?

(a3 + b3)/(a + b) = (a + b)*(a2 - ab + b2)/(a + b) = (a2 - ab + b2)


How do you rearrange v squared equals b squared bracket a squared - x squared bracket to make x the subject?

v2 = b2 (a2 - x2)Divide each side by b2 :v2/b2 = a2 - x2Subtract a2 from each side:v2/b2 - a2 = -x2Multiply each side by -1 :x2 = a2 - v2/b2Take the square root of each side:x = ± sqrt ( a2 - v2/b2 )


The formula c2 equals a2 plus b2 tells the relationship between the lengths of the sides in a right triangle what is it known as?

The Theorem of Pythagoras.